2021
DOI: 10.2196/17189
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of the Pregnancy, Exercise, and Nutrition Research Study With Smartphone App Support (PEARS) and the Use of Mobile Health in a Mixed Lifestyle Intervention by Pregnant Obese and Overweight Women: Secondary Analysis of a Randomized Controlled Trial

Abstract: Background Dietary interventions can improve pregnancy outcomes among women with increased BMI. Although the interest in mobile health interventions is growing, little is known about the acceptability of smartphone apps to support lifestyle interventions in such a cohort. Objective We aimed to assess the acceptability of the pregnancy, exercise, and nutrition research study with smartphone app support (PEARS) and the use of mobile health in a mixed life… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…The first one, which represented approximately half of the sample, was optimistically engaged, involved light-heartedness toward health, loyalty toward healthcare, and eagerness to adopt eHealth. These results are in line with other studies that also show that participants with low SES can engage in eHealth interventions [ 30 , 31 , 32 , 33 ]. The second attitude, embodied roughly a quarter of the sample, were doubtfully disadvantaged, feeling hesitance toward eHealth adoption.…”
Section: Discussionsupporting
confidence: 92%
“…The first one, which represented approximately half of the sample, was optimistically engaged, involved light-heartedness toward health, loyalty toward healthcare, and eagerness to adopt eHealth. These results are in line with other studies that also show that participants with low SES can engage in eHealth interventions [ 30 , 31 , 32 , 33 ]. The second attitude, embodied roughly a quarter of the sample, were doubtfully disadvantaged, feeling hesitance toward eHealth adoption.…”
Section: Discussionsupporting
confidence: 92%
“…The studies included were randomized controlled trials (RCTs) [ 23 , 30 - 40 ], observational studies [ 41 - 56 ], and design studies [ 57 - 77 ]. Several RCTs and observational studies evaluated eHealth interventions on health outcomes (eg, BMI, blood pressure, and hemoglobin A 1c ) [ 30 , 34 , 35 - 37 , 40 , 43 , 45 , 47 , 48 , 53 , 78 ], nutrition-related behavior outcomes [ 32 , 38 , 39 , 79 , 80 ], physical activity–related outcomes, smoking-related outcomes [ 23 , 31 , 46 , 51 , 81 , 82 ], usage outcomes [ 33 , 49 , 54 ], and reach [ 44 ], as well as feasibility and acceptability outcomes [ 47 , 80 ] ( Multimedia Appendix 3 ). Design studies examined recruitment [ 57 ], usability, feasibility [ 57 - 65 ], development, or acceptability of eHealth interventions [ 58 - 60 , 64 , 65 , 67 , 68 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the various stages of the development and evaluation of the intervention (ie, problem definition, development, and implementation for the study) [ 48 , 50 , 59 , 60 , 64 , 66 , 69 , 70 , 84 ], several studies involved stakeholders, which included family members, experts, key informants [ 50 , 61 , 69 , 75 , 84 , 86 ], health professionals, and end users [ 48 , 54 , 64 - 66 , 68 - 70 , 73 , 75 , 83 ]. However, some studies provided little information on the identification of stakeholders and did not clarify the level of involvement of stakeholders and end users [ 37 , 44 , 50 , 56 , 66 , 70 , 78 , 79 , 81 , 83 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent meta-analysis has focused on the use of smartphone-based interventions to promote maternal health behaviours and maternal-foetal health outcomes, and indicated that multimodal interventions that also include another method of communication seem to have the highest effectiveness in reducing GWG [ 49 ]. Regarding smartphone applications (apps), non-time-consuming, concise, and practical information and advice are valued by participants [ 50 ], and apps may help overcome some barriers caused by socioeconomic gaps by being easily accessible to all women [ 50 ]. Overall, the above-mentioned aspects could be interesting approaches for the design of future trials, and might be able to improve child health outcomes by increasing the intervention effect on maternal health and lifestyle during pregnancy.…”
Section: Discussionmentioning
confidence: 99%